Electrochemical Synthesis of Nickel Hydroxide Ni(OH)2 Nanoparticles Solution for Detecting Mercury (Hg) - Fauziatul Fajaroh; Yanatra Budi Pramana; Krisyanti Budipramana; Djoko Adi Walujo; Marianus Subandowo; Indah Nurhayati (JC-T (Journal Cis-Trans): Jurnal Kimia dan Terapannya, 2021)
Nickel hydroxide Ni(OH)2  nanoparticles were used as sensors for mercury (Hg) in water using a UV-Vis spectrophotometer instrument. The synthesis of Ni(OH)2  nanoparticles was carried out by electrochemical method using nickel plates as anode and cathode and  the process was operated at  constant voltage of 25 V for 30 minutes. In this study, 2 variations of the concentration of Ni(OH)2  nanoparticles were used, namely (5 mL and 4 mL) to detect mercury at concentrations of 0 ppm, 10 ppm, 20 ppm, 30 ppm, 40 ppm, and 50 ppm. Changes in the absorbance value of Ni(OH)2  nanoparticles will be observed. From the observations, there was a decrease in the absorbance value of Ni(OH)2  nanoparticles along with the increase in mercury concentration. The decrease in the absorbance value of Ni(OH)2  nanoparticles is directly proportional to the amount of mercury concentration. The detection limit value was obtained at a volume of 5 mL and 4 mL are 42 ppm, and 75.8  ppm.